2015
DOI: 10.1016/j.physletb.2014.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Superfluid phases of triplet pairing and rapid cooling of the neutron star in Cassiopeia A

Abstract: In a simple model it is demonstrated that the neutron star surface temperature evolution is sensitive to the phase state of the triplet superfluid condensate. A multicomponent triplet pairing of superfluid neutrons in the core of a neutron star with participation of several magnetic quantum numbers leads to neutrino energy losses exceeding the losses from the unicomponent pairing. A phase transition of the neutron condensate into the multicomponent state triggers more rapid cooling of superfluid core in neutro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…Nucleonic stellar models (i.e., those containing neutrons, protons, and electrons) attribute the rapid cooling to the onset of Cooper pair-breaking process in the neutron superfluid component [17][18][19][20][21][22]. An alternative nucleonic model of Ref.…”
Section: Cooling Of Compact Starsmentioning
confidence: 99%
“…Nucleonic stellar models (i.e., those containing neutrons, protons, and electrons) attribute the rapid cooling to the onset of Cooper pair-breaking process in the neutron superfluid component [17][18][19][20][21][22]. An alternative nucleonic model of Ref.…”
Section: Cooling Of Compact Starsmentioning
confidence: 99%
“…The nematic phase has a continuous degeneracy 29 which is solved by either magnetic field or 6th order terms in the GL free energy, and the uniaxial nematic (UN) phase is favored at zero temperature while D 2 -biaxial nematic (BN) and D 4 -BN phases are favored for finite and strong magnetic fields, respectively 30 , relevant for magnetars. Low-energy excitations in 3 P 2 superfluids affect the cooling process by neutrino emission [31][32][33][34][35][36][37][38][39][40][41][42] . The rapid cooling due to 3 P 2 superfluids was studied for Cassiopeia A [43][44][45] , but a direct proof of the existence of the 3 P 2 superfluidity is yet elusive.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, superfluid gaps in a generic Gaussian form are completely phenomenological, ignoring sophisticated adjustments necessary for some realistic models. For instance, it has been shown that cooling rate can have remarkable dependence on the multicomponent phase state of 3 P 2 superfluid neutrons [81]. In addition, as mentioned earlier, exotic matter may lead to exceedingly different interpretation of thermal states if they are present in neutron stars.…”
mentioning
confidence: 95%